IMPLEMENTASI KHIYAR SYARAT DALAM PRAKTIK JUAL BELI BARANG ELEKTRONIK DI TOKO SBC NGORO JOMBANG - Ariusnawati, Umi Fitri; Azizah, Ninik (Irtifaq, 2022)
Abstract: This article discusses the implementation of Khiyar requirements in the practice of buying and selling electronic goods at the SBC Ngoro Jombang store. The study used qualitative field research methods with observation and interview data collection techniques (interviews) and analyzed using normative methods. The results of the study show that both the business owners through the employees have provided goods of good quality, have explained in detail the actual conditions, and provide guarantees (khiyar requirements) on each item, so that if there is damage and there are defects in the goods after the occurrence of contract, the buyer is welcome to report again to the store for further action on the goods. The system and practice of buying and selling electronic goods at the SBC Ngoro Jombang store is carried out with Cash, DP, and credit. The implementation of the khiyar conditions is also in accordance with the provisions that apply in fiqh muamalah. Where the khiyar right is granted, to continue or cancel the sale and purchase transaction. Keywords: Khiyar Terms, SBC Store